International Law and International Relations: Quo Vadis? - Oztig, Lacin Idil (SAGE PUBLICATIONS INC, 2025)
The wars in Ukraine and Gaza poignantly reveal the inadequacy of the current international system in maintaining peace. The United Nations faces major limitations due to the absence of enforcement mechanisms and disagreement among permanent members of the Security Council. Stronger global cooperation to enhance the international system's ability to prevent and resolve wars and conflicts seems like a utopia, but it is necessary for the sake of humanity. The world needs a reimagined international system that prioritizes diplomacy and mediation over military intervention. There is a pressing need for new visions of peace and a closer dialogue between International Law and IR. This review essay critically examines the dialogue between the two disciplines since the interwar period. It highlights that liberal internationalism constituted an important intersection point between the two disciplines during the interwar period. Although the two disciplines grew apart after World War II, the post-Cold War period has witnessed a renewed interdisciplinary dialogue. However, despite this dialogue, scholars of both disciplines lack conversations on novel visions of peace. The complex and evolving challenges of our time urgently require new perspectives on peace beyond mainstream theories and methods. The essay concludes by suggesting that scholars of both disciplines should combine their experience and perspectives to develop innovative ideas for peace.
Keywords: International Law; International Relations; liberal internationalism; interdisciplinary dialogue; peace; WALTHER SCHUCKING